(untitled) (Horizontes de Enfermería, 2018)
In the article, we analyze spending on alternative and conventional medicine in the four regions of Ecuador. Th e objective of the study was to determine the diff erences between use and costs of conventional versus alternative medicine in the four regions of Ecuador: Coast, Sierra, Amazon and Insular Region. For the present study we used a database of the National Institute of Statistics and censuses, called Survey of Living Conditions. Th e study is representative, being carried out in all provinces and areas of the country, taking into account a total of 29,052 households, in which all members of a minimum age of 12 years are interviewed. Th e most outstanding results are in the Amazon, the median invested in alternative medicine exceeds the median of conventional medicine spending, this may be due to a high percentage of indigenous peoples, who traditionally would use alternative medicines, and the provision of health services are scarcer.